Breaking down barriers: the beginnings of women's practice in Mexican taekwondo (1972-1992) - López Gallo Gocchi, Edgar Iván (Revista de Artes Marciales Asiáticas, 2026)
The female contribution has been fundamental for the successful development of Mexican taekwondo, not only in its competitive contribution, but also in its popularization and teaching. However, things were not easy for the young women who in the 1970s and 1980s began to practice this discipline, since they had to overcome the historical inequality related to the sex-gender system, machismo and the lack of sports support, factors that slowed down —although they did not stop— their martial and sports development. This article reconstructs the beginnings of taekwondo practice of six women, most of them members of the Moo Duk Kwan organization, and the difficulties they faced in their sport practice. The text begins with a brief introduction in which the objectives, hypotheses, a brief state of the question and the methodology used are presented, and then some changes in the lives of women in Mexico City at the end of the 1960s. It then focuses on the experiences of six Mexican taekwondo pioneers. Finally, some brief final considerations are presented. The text begins with a brief introduction that, among other things, highlights the contribution of women in Mexican taekwondo and presents the sources used in the research; to then address the arrival of jiu-jitsu and judo in Mexico, first modern Eastern martial arts practiced in the country. He then presents some social and cultural changes in Mexico at the end of the 1960s, then focuses on the experiences of six Mexican taekwondo pioneers and a precursor to sports psychology. Finally, some final considerations are presented.